Pembinaan Warga Gereja dan Keluarga terhadap Anak dalam Membentuk Iman dan Berkarakter Kristiani - Febi Finensya Tambunan; Jelita Marsyah Sinaga; Mickael Ria Elisabet Bancin (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
This paper investigates various forms of church training for children, highlighting the central role of the family as the primary foundation. Based on a theological interpretation of Job 5:18 and an understanding of the family as a "mini church," this article explores how the family functions as the primary agent in instilling Christian values ​​through education, character education, faith and moral cultivation, and parental role models. In addition, this paper identifies the unique characteristics of children in terms of nature, needs, physical, mental, moral, psycho-social, and faith development that need to be considered in designing effective training strategies. Furthermore, this article outlines the main materials of child training and various implementation strategies that can be applied by churches and families, including increasing Sunday school services, age grouping, dexterity training, utilization of literature, emphasizing God's love and calling, and teaching principles from Proverbs 22:6. This study emphasizes the importance of a deep understanding of children and the development of empathy in the effort to foster the next generation of church members who are faithful and have Christian character.